Erkennung von Patienten mit hohem Risiko für baldige RA (Aktuelle Rheumatologie, 2017)
Nam JL et al. Enriching case selection for imminent RA: the use of anti-CCP antibodies in individuals with new non-specific musculoskeletal symptoms – a cohort study.